VEGF receptor trafficking in angiogenesis. (19th November 2009) - Scott, Alice; Mellor, Harry
Abstract : The intracellular trafficking of receptors provides a way to control the overall sensitivity of a cell to receptor stimulation. These sorting pathways are also used to shape the balance of signals that are generated in response to receptor activation. The major pro-angiogenic growth factor receptor is VEGFR2 (vascular endothelial growth factor 2). VEGFR2 activates a very similar set of signalling pathways to other RTKs (receptor tyrosine kinases); however, its intracellular trafficking is very different. Furthermore, VEGFR2 can form a complex with a range of different angiogenic regulators that in turn regulate the trafficking of VEGFR2 through the endosomal pathway. This regulated trafficking of VEGFR2 has important consequences for angiogenic signalling and is a clear demonstration of how the endosomal pathway plays a critical role in connecting receptor signalling pathways to cellular events.